Tire and vehicle dynamics / Hans B. Pacejka - Pacejka, Hans B.
This book covers everything you need to know about pneumatic tires and their impact on vehicle performance, including mathematic modeling and its practical application. Written by the acknowledged world authority on the topic and the name behind the most widely used model, Pacejka’s ‘Magic Formula’. Updated with the latest information on new and evolving tire models to ensure you can select the right model for your needs, apply it appropriately and understand its limitations